A Case of Onychomycosis Caused by Rhodotorula glutinis - Hatice Uludag Altun; Tuba Meral; Emel Turk Aribas; Canan Gorpelioglu; Nilgun Karabicak (Case Reports in Dermatological Medicine)
Rhodotorula spp. have emerged as opportunistic pathogens, particularly in immunocompromised patients. The current study reports a case of onychomycosis caused by Rhodotorula glutinis in a 74-year-old immunocompetent female. The causative agent was identified as R. glutinis based on the pinkish-orange color; mucoid-appearing yeast colonies on Sabouraud Dextrose Agar at 25°C; morphological evaluation in the Corn Meal-Tween 80 agar; observed oval/round budding yeast at 25°C for 72 hours; no observed pseudohyphae; positive urease activity at 25°C for 4 days; and assimilation features detected by API ID 32C kit and automated Vitek Yeast Biochemical Card 2 system. Antifungal susceptibility test results were as follows: amphotericin B (MIC = 0.5 µg/mL), fluconazole (MIC = 128 µg/mL), itraconazole (MIC = 0.125 µg/mL), voriconazole (MIC = 1 µg/mL), posaconazole (MIC = 0.5 µg/mL), anidulafungin (MIC = 0.5 µg/mL), and caspofungin (MIC = 16 µg/mL). Antifungal therapy was initiated with oral itraconazole at a dose of 400 mg/day; seven-day pulse therapy was planned at intervals of three weeks. Clinical recovery was observed in the clinical evaluation of the patient before the start of the third cure. Although R. glutinis has rarely been reported as the causative agent of onychomycosis, it should be considered.